Projected climate oligotrophication of the Adriatic marine ecosystems - Mentaschi, Lorenzo; Lovato, Tomas; Butenschön, Momme; Alessandri, Jacopo; Aragão, Leonardo; Verri, Giorgia; Guerra, Roberta; Coppini, Giovanni; Pinardi, Nadia (Frontiers in Climate, 2024)
The Adriatic Sea hosts diverse marine ecosystems, characterized by rich biodiversity and unique ecological dynamics. Its intricate coastal habitats and open waters support a range of species and contribute to the region's ecological and economic significance. Unraveling the consequences of the ongoing climate changes on this delicate environment is essential to ensure the future safeguard of this basin. To tackle this problem, we developed a biogeochemical model for the entire basin, with a horizontal resolution of about 2 km and 120 vertical levels, forced by the projections of atmosphere, hydrology and ocean circulation between 1992 and 2050, under emission scenario RCP8.5. The changes projected between 2031-2050 and 1992-2011 were evaluated on ecoregions characterized by different trophic conditions, identified using a k-medoid classification technique. The results point towards a generalized oligotrophication of the basin, especially intense in the northern estuarine areas, driven by a substantial decrease in river discharge projected for the rivers of the Po Plain. This scenario of unproductive and declining resources, together with the ongoing warming, salinization, and acidification of marine waters, cast doubt on the long-term resilience of the Northern Adriatic food web structure, which has evolved to thrive in high trophic conditions. The outcome of this study provides the stakeholders with a tool to understand how potential long-term decreases in the regimes of the Northern Adriatic rivers could affect the marine ecosystem and its goods and services in the future.